Surface physics of semiconducting nanowires. Issue 1 (February 2016) - Amato, Michele; Rurali, Riccardo
Abstract: Semiconducting nanowires (NWs) are firm candidates for novel nanoelectronic devices and a fruitful playground for fundamental physics. Ultra-thin nanowires, with diameters below 10 nm, present exotic quantum effects due to the confinement of the wave functions, e.g. widening of the electronic band-gap, deepening of the dopant states. However, although several reports of sub-10 nm wires exist to date, the most common NWs have diameters that range from 20 to 200 nm, where these quantum effects are absent or play a very minor role. Yet, the research activity on this field is very intense and these materials still promise to provide an important paradigm shift for the design of emerging electronic devices and different kinds of applications. A legitimate question is then: what makes a nanowire different from bulk systems? The answer is certainly the large surface-to-volume ratio. In this article we discuss the most salient features of surface physics and chemistry in group-IV semiconducting nanowires, focusing mostly on Si NWs. First we review the state-of-the-art of NW growth to achieve a smooth and controlled surface morphology. Next we discuss the importance of a proper surface passivation and its role on the NW electronic properties. Finally, stressing the importance of a large surface-to-volume ratio and emphasizing the fact that in a NW the surface is where most of the action takes place, we discuss molecular sensing and molecular doping.